2017
DOI: 10.1016/j.bbadis.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil derived microparticles increase mortality and the counter-inflammatory response in a murine model of sepsis

Abstract: Although advances in medical care have significantly improved sepsis survival, sepsis remains the leading cause of death in the ICU. This is likely due to a lack of complete understanding of the pathophysiologic mechanisms that lead to dysfunctional immunity. Neutrophil derived microparticles (NDMPs) have been shown to be the predominant microparticle present at infectious and inflamed foci in human models, however their effect on the immune response to inflammation and infection is sepsis has not been fully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 68 publications
1
46
0
Order By: Relevance
“…Microvesicles were isolated as previously described 19 . In brief, bronchoalveolar (BAL) fluid was collected from sham and post burn day 1 (PBD1) mice and centrifuged at 450 × g for 10 minutes at room temperature to form a cell pellet.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microvesicles were isolated as previously described 19 . In brief, bronchoalveolar (BAL) fluid was collected from sham and post burn day 1 (PBD1) mice and centrifuged at 450 × g for 10 minutes at room temperature to form a cell pellet.…”
Section: Methodsmentioning
confidence: 99%
“…These signals depend largely on the parent cell, which can be lymphocytes, platelets, leukocytes, endothelial and epithelial cells 14,15 . Platelet-derived MVs are the most abundant whereas neutrophil-derived MVs are the dominant type generated at the site of infection 14,19,20 . Neutrophil-derived MVs have been shown to increase the inflammatory response and increase mortality 14,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caldwell and colleagues report that neutrophil derived microparticles can influence the host response in sepsis induced by cecal ligation and puncture (CLP) [7]. The microparticles can modulate target cell function by interaction with cell surface receptors or intra cellular delivery of the cargo containing bioactive factors such as miRNA.…”
mentioning
confidence: 99%
“…The microparticles can modulate target cell function by interaction with cell surface receptors or intra cellular delivery of the cargo containing bioactive factors such as miRNA. According to the authors, neutrophil-derived microparticles are the most predominant microparticles observed in sepsis [7] and administration of these microparticles into the mice during CLP increased mortality. The authors conclude that neutrophil-derived microparticles augment immune dysfunction in sepsis by inhibiting innate immune response mediated by neutrophils and macrophages.…”
mentioning
confidence: 99%